2020
DOI: 10.1101/2020.07.27.222588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic control over feedback regulatory mechanisms improves NADPH fluxes and xylitol biosynthesis in engineeredE. coli

Abstract: We report improved NADPH flux and xylitol biosynthesis in engineered E. coli. Xylitol is produced from xylose via an NADPH dependent reductase. We utilize two-stage dynamic metabolic control to compare two approaches to optimize xylitol biosynthesis, a stoichiometric approach, wherein competitive fluxes are decreased, and a regulatory approach wherein the levels of key regulatory metabolites are reduced. The stoichiometric and regulatory approaches lead to a 16 fold and 100 fold improvement in xylitol producti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…As mentioned above we have previously reported the identification of valves which lead to deregulation of glucose uptake (GltA), acetyl-CoA flux (Zwf), and NADPH synthesis through the membrane bound transhydrogenase (FabI). 21,22 Additionally, we have reported that proteolytic degradation of the soluble transhydrogenase (UdhA) can improve NADPH pools. 21 As depicted in Figure 2a, alanine production requires pyruvate and NADPH, so we designed strains with combinations of valves reducing levels of GltA ("G" Valves), FabI ("F" Valves), and UdhA ("G" Valves).…”
Section: Strain Designmentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned above we have previously reported the identification of valves which lead to deregulation of glucose uptake (GltA), acetyl-CoA flux (Zwf), and NADPH synthesis through the membrane bound transhydrogenase (FabI). 21,22 Additionally, we have reported that proteolytic degradation of the soluble transhydrogenase (UdhA) can improve NADPH pools. 21 As depicted in Figure 2a, alanine production requires pyruvate and NADPH, so we designed strains with combinations of valves reducing levels of GltA ("G" Valves), FabI ("F" Valves), and UdhA ("G" Valves).…”
Section: Strain Designmentioning
confidence: 99%
“…21,22 Additionally, we have reported that proteolytic degradation of the soluble transhydrogenase (UdhA) can improve NADPH pools. 21 As depicted in Figure 2a, alanine production requires pyruvate and NADPH, so we designed strains with combinations of valves reducing levels of GltA ("G" Valves), FabI ("F" Valves), and UdhA ("G" Valves). Firstly, we evaluated the impact of silencing both promoters driving gltA expression.…”
Section: Strain Designmentioning
confidence: 99%
See 3 more Smart Citations